The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1007/s00381-013-2173-x
|View full text |Cite
|
Sign up to set email alerts
|

Acute two-compartment low pressure hydrocephalus—a case report

Abstract: A case of an 8-year-old-boy with shunt-dependent occlusive hydrocephalus after resection of a cerebellar medulloblastoma is presented, who experienced repeated episodes of severe neurologic deterioration with signs and symptoms of raised intracranial pressure after spinal tapping. However, intracranial pressure was recorded within low ranges, only up to the opening pressure of the implanted adjustable shunt valve. Multiple shunt revisions were performed, until the condition was recognized as acute normal press… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…7 LPH may either occur spontaneously or as a result of CSF egress from the skull base, spinal intradural procedures, or lumbar punctures. [2][3][4][5]10,11 Patients usually present with symptoms similar to those seen in the more prevalent high-pressure hydrocephalus. Headaches, nausea, cranial neuropathies, disturbances in mental status, and decreased consciousness are often seen.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…7 LPH may either occur spontaneously or as a result of CSF egress from the skull base, spinal intradural procedures, or lumbar punctures. [2][3][4][5]10,11 Patients usually present with symptoms similar to those seen in the more prevalent high-pressure hydrocephalus. Headaches, nausea, cranial neuropathies, disturbances in mental status, and decreased consciousness are often seen.…”
Section: Discussionmentioning
confidence: 99%
“…Many patients have a less than effective communication between the subarachnoid, ventricular, and spinal compartments. [5][6][7] The drop in ICP following a lumbar puncture is considerably smaller in those patients with a block at the cisterna magna, since the amount of CSF that actually passes through the obstruction is negligible. 18 Barami et al 19 studied the pressure volume index in 20 shunted patients with hydrocephalus and demonstrated that the shift of cerebral subarachnoid CSF into the spinal canal is too small to account for the necessary drop in ICP needed to modify the CSF to venous pressures relationships.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations